Isoperistaltic versus antiperistaltic uncut Roux-en-Y anastomosis after distal gastrectomy for gastric cancer: a propensity score matched analysis - Hangtian, Cui (BMC Surg, 2020)
BACKGROUND: The uncut Roux-en-y anastomosis (URYA) has some clinical advantages after distal gastrectomy (DG). Little evidence exists regarding the influence of peristalsis on this anastomosis. We aimed to evaluate short-term outcomes of isoperistaltic URYA (iso-URYA) comparing with antiperistaltic URYA (anti-URYA) after DG. METHOD: Patients who underwent URYA for gastric cancer (GC) between January 2016 and December 2018 were selected from Shanghai Changhai Hospital, Navy Medical University. Short-term outcomes were compared between iso-URYA group and anti-URYA group after 1:1 propensity score matching (PSM). RESULT: A total of 612 patients were selected. 392 patients underwent iso-URYA and 220 patients underwent anti-URYA. After PSM, 183 patients for each group were included in the final analysis. No differences were found between them in terms of short-term complications, nutritional status and quality of life 1 year after surgery. Endoscopic examination showed that anti-URYA group had more severe gastritis (P = 0.036). In addition, the recanalization rate was significantly higher when the afferent loop was blocked by stapler. CONCLUSION: The iso-URYA and anti-URYA group present similar results in short term outcomes. Ligation blocking afferent loop leads to lower recanalization rate.